Intraspecific diversity of durum wheat (Triticum durum Desf.): a unif ied classif ication - О. A. Lyapunova (Вавиловский журнал генетики и селекции)
The Department of Wheat Genetic Resources of the All-Russian Research Institute of Plant Genetic Resources (VIR) had developed and published in 1979 a classification of the genus Triticum L., which is based on the genomic composition of species and the presence or absence of a number of main genes that govern the “classification” traits. The grounds have been laid by F. Körnicke and J. Percival, and supplemented by N.I. Vavilov and K.A. Flaksberger. The classification, which is most often referred to as the “Classification of Triticum by Dorofeev et al.”, belongs to a number of the main modern classifications of the genus. This is the world’s first standardized system that contains all known intraspecific (infraspecific) taxa of wild and cultivated wheat species. A detailed classification makes it possible to identify a wide variety of forms in the genus Triticum L. and its individual species, which is especially important for collections preserved in genetic seed banks. The use of the intraspecific classification of the genus Triticum L. greatly simplifies the identification of the VIR collection accessions introduced from various sources or checking accession identity after regeneration in the field. However, the direct use of such a voluminous classification meets several difficulties. Therefore, we propose a unified intraspecific classification of durum wheat, based on the description of only 16 main botanical varieties out of 131 described so far, which have complexes of morphological traits of the spike and kernel that occur most frequently in durum wheat collections. The remaining 115 botanical varieties, which have additional traits, get their name by the addition of the abbreviated Latin name of one or another additional trait to the main name. Having mastered this way of describing the morphological traits of accessions, any user can easily navigate oneself in the systematized intraspecific diversity of collections. The purpose of this work is to acquaint the reader with the intraspecific classification of durum wheat (Triticum durum Desf.) developed at VIR and to offer its simplified version, which is based on the identification of the main and additional morphological traits of the spike and kernel.